Patient-reported outcome measures in arthroplasty registries - Rolfson, O; Eresian Chenok, K; Bohm, E; Lubbeke, A; Denissen, G; Dunn, J; Lyman, S; Franklin, P; Dunbar, M; Overgaard, S; Garellick, G; Dawson, J (Taylor and Francis, 2016)
The International Society of Arthroplasty Registries (ISAR) Steering Committee established the Patient-Reported Outcome Measures (PROMs) Working Group to convene, evaluate, and advise on best practices in the selection, administration, and interpretation of PROMs and to support the adoption and use of PROMs for hip and knee arthroplasty in registries worldwide. The 2 main types of PROMs include generic (general health) PROMs, which provide a measure of general health for any health state, and specific PROMs, which focus on specific symptoms, diseases, organs, body regions, or body functions. The establishment of a PROM instrument requires the fulfillment of methodological standards and rigorous testing to ensure that it is valid, reliable, responsive, and acceptable to the intended population. A survey of the 41 ISAR member registries showed that 8 registries administered a PROMs program that covered all elective hip or knee arthroplasty patients and 6 registries collected PROMs for sample populations; 1 other registry had planned but had not started collection of PROMs. The most common generic instruments used were the EuroQol 5 dimension health outcome survey (EQ-5D) and the Short Form 12 health survey (SF-12) or the similar Veterans RAND 12-item health survey (VR-12). The most common specific PROMs were the Hip disability and Osteoarthritis Outcome Score (HOOS), the Knee injury and Osteoarthritis Outcome Score (KOOS), the Oxford Hip Score (OHS), the Oxford Knee Score (OKS), the Western Ontario and McMaster Universities Arthritis Index (WOMAC), and the University of California at Los Angeles Activity Score (UCLA).